1965
DOI: 10.1073/pnas.53.5.952
|View full text |Cite
|
Sign up to set email alerts
|

The action of anesthetics on excitable membranes: a quantum-chemical analysis.

Abstract: rich nuclear RNA was formed in the rats which increased their performance linearly with time during learning. Some animals showed a nonlinear performance curve. The nuclear RNA formed in the neurons of these rats had a ribosomal type of base composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

1970
1970
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 1 publication
0
32
0
3
Order By: Relevance
“…The conceptual roots of this non-empirical model go back to the work of Agin et al 41 and Cammarata et al [42][43][44][45] . Let us consider the state of thermodynamic equilibrium, and a 1:1 stoichiometry in the formation of the drug-receptor complex:…”
Section: Methods Models and Calculationsmentioning
confidence: 99%
“…The conceptual roots of this non-empirical model go back to the work of Agin et al 41 and Cammarata et al [42][43][44][45] . Let us consider the state of thermodynamic equilibrium, and a 1:1 stoichiometry in the formation of the drug-receptor complex:…”
Section: Methods Models and Calculationsmentioning
confidence: 99%
“…Ele pode representar forças dispersivas que ajudam a interação do ligante ao receptor 29 . Nesses casos esperar-se-ia um coeficiente positivo para MR. Alternativamente, uma vez que MR é, até um certo grau, uma medida de volume, ele pode medir a capacidade de o ligante distorcer a conformação do receptor para assim evitar a interação com o substrato.…”
Section: Descritores Físicos Da Estrutura Tridimensional (3d)unclassified
“…4 shows the relationship between log rx+y and log (K, Webb (11) classified the three types of interaction of two inhibitors by isobologram using fractional inhibition and empirical equations. In his treatment, summation is expressed by i1,2 = 'I + i2 -l i [3] where il,2 is the fractional inhibition when two [4] where A equals the inhibitor concentration and K is a constant.…”
Section: And 2 Are Indistinguishablementioning
confidence: 99%
“…This theory suggests that there are at least two separate modes of action among agents that show local anesthetic action: the predominant force of interaction of dissociable anesthetics is ionic, whereas the mode of action of undissociable local anesthetics is not. However, Agin et al (3) and Hersh (4) suggested that dissociable and undissociable local anesthetics may interact with living and model systems in an identical way.…”
mentioning
confidence: 99%